Differentiating a Pressure Ulcer from Acute Skin Failure in the Adult Critical Care Patient. (November 2015) - Delmore, Barbara; Cox, Jill; Rolnitzky, Linda; Chu, Andy; Stolfi, Angela
Abstract : PURPOSE: The purpose of this learning activity is to provide information regarding the differentiation between pressure ulcers and acute skin failure (ASF) in critically ill patients. TARGET AUDIENCE: This continuing education activity is intended for physicians and nurses with an interest in skin and wound care. OBJECTIVES: After participating in this educational activity, the participant should be better able to: 1. Describe the purpose, methodology and impact of this research. 2. Differentiate the pathophysiology of pressure ulcers and ASF. 3. Identify risk factors and diagnostic criteria for ASF. ABSTRACT: OBJECTIVE: To develop a statistical model to predict the development of acute skin failure in patients admitted to the intensive care unit (ICU) and to validate this model. DESIGN: Retrospective case-control, logistic regression modeling PARTICIPANTS: 552 ICU patients MAIN OUTCOME MEASURES: Intensive care unit patients with and without pressure ulcers (PrUs) were studied and compared on key variables sorted into the following categories: (1) disease status, (2) physical conditions, and (3) conditions of hospitalization. RESULTS: The variables, peripheral arterial disease (odds ratio [OR], 3.8; P = .002), mechanical ventilation greater than 72 hours (OR, 3.0; P < .001), respiratory failure (OR, 3.2; P < .001), liver failure (OR, 2.9; P = .04), and severe sepsis/septic shock (OR, 1.9; P = .02), were found to be statistically significant and independent predictors of acute skin failure in ICU patients. These variables created a predictor model for acute skin failure in the ICU. CONCLUSIONS: Lack of objective criteria to define acute skin failure presents a clinical conundrum for practitioners—the acknowledgment that skin failure exists, but no clear-cut diagnostic criteria in which to support its existence as a result of a paucity of empirical evidence. In certain populations, such as the critically ill patient, the phenomenon of acute skin failure may be occurring, and with the current level of evidence, these ulcers may be incorrectly identified as PrUs. Accurately distinguishing risk factors that lead to a PrU from factors that result in a lesion due to acute skin failure is crucial in the quest to provide evidence-based practice to patients.